Faktor-faktor yang Mempengaruhi Kinerja Bidan dalam Pelaksanaan Standar Pelayanan Antenatal di Wilayah Kerja Puskesmas Pidie - Rita Mirdahni; R. Kintoko Rochadi; Abdul Jalil Amri Arma (Serambi Saintia : Jurnal Sains dan Aplikasi, 2021)
A midwife, as a spearhead of the health development, has a direct relation to the implementation of antenatal service standart. She can be the supporting factors, but she can also be the inbiting factors of a mother’s death. The objective of the research was to find out the factors that influence midwives performance in the implementation of antenatal service standard in the working area of Pidie Puskesmas, in 2015. The research was an analitical survey with cross-sectional design. The population was 102 midwives in the working area of Pidie Puskesmas, and all of them were used as the samples. The data were collected by distributing questionnaires and conductong observation and analysed with Chi Square test and multiple logistic regression analysis. The result of the research showed that 47.1% of the respondentd had good performance and 52.9% of them had the bad performance. There was the influence of experience (p=0.010) demography (p=0.008), motivation (p=0.042), and satisfaction (p=0.012) on the respondents performance. The variable of satisfaction had the most dominant influence on midwives performance with coefficient regression value=1.636 which indicated the midwives who had the less satisfaction had the possibility of 5.135 times greater to have bad performance, compared to those who had the easy satisfaction. It is recommended that the management of Pidie Puskesmas give some rewards to the active midwives so that they can carry out their duties and functions as midwives who implement the antenatal service standard and midwives cooperate to one another to avold any conflicts. Keywords : Performance, Individual, Psychological, Organization, Midwife